An integrative test of agility, speed and skill in soccer: Effects of exercise - Bullock, W.; Panchuk, D.; Broatch, J.; Christian, R.; Stepto, N. K. (Journal of Science and Medicine in Sport, 2012)
Objectives: The aim of this study was to evaluate the effect of 45 min of soccer-specific exercise in the reactive motor skills test (RMST); a novel test which measures sprint, passing and reactive agility (RAT) performance. Design: A repeated-measures design was used to collect performance data. Methods: Forty-two high-level amateur male soccer players (age 18.5±3.5 years) were recruited. Participants were familiarised with the RMST prior to initial testing. Participants undertook 10 repetitions of the RMST before and after 45 min of soccer-specific exercise using the Loughborough Intermittent Shuttle Test. Eighteen of these participants repeated the RMST for test re-test reliability determination. Paired t-tests and effect size statistics were used to determine the effect of 45 min of intermittent exercise on RMST performance. Reliability was assessed using the standard error of measurement. Results: The exercise protocol resulted in moderate decreases of sprint. Change in total test time was trivial. The test-retest coefficient of variation for the test was 2.4 ± 0.8%. Conclusions: Soccer-specific exercise decreased sprint and reactive agility performance but improved technical skill performance on a novel, integrative and reliable test of soccer skill performance. Overall RMST performance time was largely unchanged. Change in total test time was trivial. The test-retest coefficient of variation for the test was 2.4 ± 0.8%.